2020
DOI: 10.3389/fnhum.2019.00474
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transcranial Stimulation With Direct and Alternating Current on Resting-State Functional Connectivity: An Exploratory Study Simultaneously Combining Stimulation and Multiband Functional Magnetic Resonance Imaging

Abstract: Background: Transcranial stimulation with direct (tDCS) and alternating current (tACS) has increasingly gained interest in various fields, from cognitive neuroscience to clinical investigations. Transcranial current stimulation used alone may modulate brain activity that consequently influences behaviors, without providing information on potentially induced brain activity changes. The combination of transcranial current stimulation and functional magnetic resonance imaging (fMRI) may help to address this. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 37 publications
3
41
0
Order By: Relevance
“…Whereas Keeser et al (2011) focused on the connectivity strength changes in different brain networks, other research focused on pairwise connectivity between lDLPFC and other brain regions. Using a seed-based connectivity analysis, Mondino et al (2020) showed that the lDLPFC stimulation increased resting-state functional connectivity between lDLPFC and bilateral parietal regions (IPL, SPL). IPL and SPL belong to FPCN, and therefore these findings are consistent with our finding that lDLPFC connectivity within FPCN was increased by stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas Keeser et al (2011) focused on the connectivity strength changes in different brain networks, other research focused on pairwise connectivity between lDLPFC and other brain regions. Using a seed-based connectivity analysis, Mondino et al (2020) showed that the lDLPFC stimulation increased resting-state functional connectivity between lDLPFC and bilateral parietal regions (IPL, SPL). IPL and SPL belong to FPCN, and therefore these findings are consistent with our finding that lDLPFC connectivity within FPCN was increased by stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the connectivity changes specific to lDLPFC or between lDLPFC and the networks were not directly tested in this study. In another study, connectivity analyses using lDLPFC as the seed region showed that the stimulation increased connectivity between lDLPFC and bilateral parietal regions inferior parietal lobule [IPL], superior parietal lobule [SPL]); however, this study focused on pairwise functional connectivity relationships and did not take the network structure into consideration (Mondino et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of tACS or NFB on brain plasticity have been already investigated by using fMRI (Kluetsch et al, 2014 ; Nicholson et al, 2016 ; Abellaneda-Pérez et al, 2020 ; Gundlach et al, 2020 ; Mondino et al, 2020 ; Chen et al, 2021 ), the measurement of a motor-evoked potential (MEP) by transcranial magnetic stimulation (TMS) (Ros and Gruzelier, 2011 ; Wach et al, 2013 ; Vallence et al, 2021 ). The link between EEG changes and changes in the levels of the concentration of the molecular substrates of plasticity after tACS/NFB intervention has been already studied too Lee et al, 2019 ; Wischnewski et al, 2019 ; Markiewicz and Dobrowolska, 2020 ; Riddle et al, 2020a ).…”
Section: Mechanisms Of Tacs and Nfbmentioning
confidence: 99%
“…Anti-phase tACS disturbed frontoparietal alpha synchronization compared to in-phase tACS. Previous studies have reported the potential impact of tACS on functional connectivity (29,30) and found increases in the strength of alpha synchronization with increasing memory load among the frontoparietal regions known to underlie executive and attentional functions during WM maintenance (31,32), so online tACS effects in frontoparietal alpha synchronization were also assessed. The phase lag index (PLI) was used to describe frontoparietal alpha synchronization considering its reliable estimates of phase synchronization against the presence of volume conduction (33).…”
Section: No Systematic Differences Between In-phase Tacs and Anti-phase Tacs At Pre-testmentioning
confidence: 99%